2018
DOI: 10.1186/s12878-018-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of haematological indices in predicting early iron deficiency among pregnant women in an urban area of Sri Lanka

Abstract: BackgroundEarly detection and treatment of iron deficiency during pregnancy is crucial for optimum pregnancy outcomes. Anaemia is a late indictor of iron deficiency measured as Hb < 11 g/dL, and is widely used as a proxy for iron deficiency. We aimed to evaluate the role of red cell indices as a screening tool for early detection of iron deficiency among pregnant women in an urban area of Sri Lanka.MethodA cross-sectional study was conducted among 110 apparently healthy pregnant women ≤12 weeks of gestation at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
4
18
1
4
Order By: Relevance
“…The best, though still suboptimal, conventional peripheral blood marker for iron deficiency, was MCV. Microcytosis is commonly used as a screening test for iron deficiency [34,49,50]; however, MCV has not been found to be an accurate predictor of BM-ID [10,11,48]. Our findings confirm this as MCV did not have a high sensitivity or specificity and the AUC ROC was of low diagnostic value.…”
Section: Discussionsupporting
confidence: 73%
“…The best, though still suboptimal, conventional peripheral blood marker for iron deficiency, was MCV. Microcytosis is commonly used as a screening test for iron deficiency [34,49,50]; however, MCV has not been found to be an accurate predictor of BM-ID [10,11,48]. Our findings confirm this as MCV did not have a high sensitivity or specificity and the AUC ROC was of low diagnostic value.…”
Section: Discussionsupporting
confidence: 73%
“…This observation further suggests that Ret-He may be helpful to differentiate between Hb in predicting early iron deficiency among pregnant females but reticulocyte parameters were not studied. 16 Another interesting finding observed in the present study was that cutoff of 29.4 ng Ret-He was specific (87%) for the diagnosis of IDA in pregnant females with positive predictive value of 73%. Previous studies have observed variable cutoffs of Ret-He in IDA ranging from 26 to 30.9 pg.…”
Section: Discussionsupporting
confidence: 65%
“…Rabindrakumar et al also evaluated hematological indices MCV, MCH, MCHC, and Hb in predicting early iron deficiency among pregnant females but reticulocyte parameters were not studied. 16 …”
Section: Discussionmentioning
confidence: 99%
“…One study in Sri Lanka found the MCHC to have the best sensitivity for detection of iron deficiency, compared with Hb and the other red cell indices (Rabindrakumar, et al , ). This has not been supported by UK studies (Vora et al , ) but potential biomarkers need to be further investigated to find a practical, cost effective measure for the early detection of iron depletion.…”
Section: Diagnosismentioning
confidence: 99%